Gregory of Nyssa, Homilies on the Beatitudes : an English version with commentary and supporting studies : proceedings of the Eighth International Colloquium on Gregory of Nyssa, Paderborn, 14-18 September 1998 - Drobner, Hubertus R.; Viciano, Alberto.; Gregory, of Nyssa, Saint, approximately 335-approximately 394. (Vigiliae Christianae, Supplements, 2000)
These proceedings present the first English translation of Gregory's Homilies on the Beatitudes by Stuart Hall, accompanied by a thorough commentary by Anthony Meredith, Andreas Spira, Françoise Vinel, Lucas Mateo-Seco, Thomas Böhm, Karl-Heinz Uthemann, Claudio Moreschini, and Robert Wilken. Eight more contributions by Monique Alexandre, Peter Bruns, Judith Kovacs, Salvatore Lilla, Friedhelm Mann, Alden Mosshammer, Elias Moutsoulas, and Lucian Turcescu focus on further general and particular topics of the homilies as their eschatology, the meaning of the word makarios in all of Gregory's works, the notion of justice, and Gregory's Theology of Adoption, as well as their relationship to Syriac theology, Clement of Alexandria, Neoplatonism, and Gregory's Homilies on the Song of Songs . The third and fourth part add ten studies reflecting the present overall state of Gregorian research.